Anatomo-arthroscopic approach of the lateral ligament complex of the ankle - Batista, Jorge Pablo; Arrondo, Guillermo Martin; Matías-Joannas, Germán; Casola, Leandro; Logiocco, Lucas Daniel; Cangiano, Lucía Verónica (Journal of the Foot & Ankle, 2022)
Injuries of the lateral ligament complex of the ankle have become increasingly frequent over the last years due to increase in sports practice among the population. These injuries present with good outcomes when treated conservatively. However, 20-25% of patients experience persistent pain or instability and should be approached surgically. Countless open surgical techniques have been published over the last 50 years. Currently knowledge on superficial, deep, and arthroscopic anatomy of ankle has allowed for the development of completely arthroscopic procedures to treat chronic lateral instability of the ankle. The aim of this article is to describe the superficial and deep anatomy of lateral ligament complex of the ankle, specifically from the arthroscopic point of view, for it to be applied to the multiple currently described surgical procedures. Level of Evidence III; Therapeutic Studies; Comparative Retrospective Study.